1976
DOI: 10.1128/aem.32.3.443-444.1976
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Ochratoxin A by a Ruminant

Abstract: The fate of ochratoxin A during incubation with contents from the four stomachs ofthe cow was studied. It was concluded that ochratoxin A was cleaved into the nontoxic ochratoxin a and phenylalanine by the contents from all but the abomasum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(36 citation statements)
references
References 6 publications
4
29
0
3
Order By: Relevance
“…These results are consistent with the findings of six ruminating 12-week-old calves, which were fed diets containing 390 to 540 μg OTA/kg for 87 days and did not show any evidence of kidney or liver damage (Patterson et al 1981). Since it was concluded that cows may degrade OTA in feeds contaminated with up to 12 mg/kg of the toxin by the aid of rumen microorganisms (Hult et al 1976), it was assumed that the rumen microorganisms protected the cows against its toxic effects. The results obtained in this study show that the repeated ingestion of diets containing up to 100 μg/kg of OTA does not cause an adverse effect on the body condition of cows.…”
Section: Body Conditionsupporting
confidence: 87%
“…These results are consistent with the findings of six ruminating 12-week-old calves, which were fed diets containing 390 to 540 μg OTA/kg for 87 days and did not show any evidence of kidney or liver damage (Patterson et al 1981). Since it was concluded that cows may degrade OTA in feeds contaminated with up to 12 mg/kg of the toxin by the aid of rumen microorganisms (Hult et al 1976), it was assumed that the rumen microorganisms protected the cows against its toxic effects. The results obtained in this study show that the repeated ingestion of diets containing up to 100 μg/kg of OTA does not cause an adverse effect on the body condition of cows.…”
Section: Body Conditionsupporting
confidence: 87%
“…Regarding OTA, several reports describe OTA degrading activities of the microbial flora of the mammalian gastrointestinal tract including rumen microbes of cow and sheep (Galtier and Alvinerie 1976;Hult et al 1976;Park et al 1988) and microbes living mainly in the caecum and large intestine of rats (Madhyastha et al 1992). The human intestinal microflora can also partially degrade OTA (Akiyama et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…OTA can be degraded by enzymes (especially proteolytic enzymes) and different microbial populations in intestines. 22,23 In ruminants, OTA is degraded by microbes in the 3 forestomach compartments (rumen, reticulum, omasum), which makes ruminants less sensitive to OTA. Although in nonruminants, microbial degradation basically takes place in large intestine after absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, OTA is more dangerous in nonruminants and pig is particularly sensitive among farmed animals. 22 Thus, the objectives of this article were to verify OTA-induced the nephrotoxicity and immunotoxicity and to study the effects of OTA on ER stress, p38, and ERK1/2 MAPK signaling pathway expression, and autophagy in kidney and spleen of weaned pigs.…”
Section: Introductionmentioning
confidence: 99%